MODERN APPROACHES TO THE PROPHYLAXIS OF TRANSIENT DIARRHEA IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The article discusses the etiology, pathogenesis, risk factors, and preventive measures of acute diarrhea in children. The disease is highly prevalent among children under five years of age and may lead to dehydration and severe complications. Based on literature analysis, the importance of hygiene, rational nutrition, breastfeeding, safe drinking water, sanitation, and vaccination is highlighted. A comprehensive preventive approach significantly reduces morbidity and complications.